Tantangan serta Hambatan yang dihadapi Dunia Pendidikan Kristen di Masa Lalu, Sekarang dan pada Perspektif Masa Depan; Baik di Keluarga, Gereja, serta Sekolah - Asido Gabe Paruntungan Pasaribu (Neolectura, 2022)
The history of Christian religious teaching has changed in the form of implementation. These changes are influenced by the surrounding environment, culture, different cultures, but have the same position as Indonesian people. Christian religious education starts from family, church, and school. Thus the writing of this article aims to analyze how the challenges of the world of Christian religious education are. The author uses a qualitative method for the process of writing this article, in which the sources are collected from various written sources, such as books, websites that support the data, which are related to the title of the research being studied. The results of this study are to provide an understanding that Christian religious education has obstacles and challenges that can be resolved through a Christian approach in the family, church, and school.